ENT 530 Social media report / Nur Syakirah Shuib - Shuib, Nur Syakirah (2021)
"Sambal Warisan Opah" is an online-based entrepreneurship that sells homemade products based on instant sambal essence. I chose this brand and product because I want to promote this product better known by our society because it is a product that is easy to use and to further raise the name of this product because it is a bumiputera product. In addition, the product released is the first product of this young entrepreneur. I am requesting permission from Mr. Mustaqim Ahmad Fuad to introduce this product again through social media such as the facebook website and account page which is "sambalwarisanopah".